Sharp expansion of the cesarean delivery uterine incision in women with previous cesarean section scars. Issue 10 (22nd October 2022) - Chatzipapas, Ioannis; Diakosavvas, Michail; Angelou, Kyveli; Kypriotis, Konstantinos; Douligeris, Athanasios; Kathopoulis, Nikolaos
Abstract: Although the blunt uterine incision expansion during a low‐transverse cesarean delivery has prevailed over the sharp technique, the latter should not be completely abandoned. The sharp method with scissors should be considered when managing patients with previous cesarean sections, although more studies are required for a definite answer. Abstract : During a low‐transverse cesarean delivery, the blunt technique is the preferred modality, concerning the maternal outcomes. However, the sharp expansion of the lower uterine segment incision could have a role when delivering women with previous cesarean scars, since it is more controlled, without unintended transverse and vertical extensions, thus resulting in better closure. Nonetheless, more research is required for a definite answer to be given.